The Moderating Effect of CEO Attributes on The Relationship Between CSR and CEO Power And Company Performance. - Afni, Naila; Makarnayawati, Makarnayawati; Juliardi, Dodik (Universitas Negeri Malang, 2025)
Prior empirical studies have shown how CEO power affects firm performance and (CSR). The purpose of this study is to investigate the relationship between CEO quality and firm success by minimizing the influence of CSR and CEO power. To assess data from mining companies listed on the Indonesia Stock Exchange, Smart PLS was utilized. According to the research’s findings, the influence of CSR on company success and CEO authority are not influenced by factors like tenure, age, or education. A company's positive image among the public, investors, and other stakeholders is reinforced by CSR disclosure, which is frequently seen to improve a company's reputation. But according to the research's findings, a number of CSR elements actually take attention away from improving business success. Stakeholders should consider this research when assessing the effect of CSR disclosure on business performance. To improve corporate legitimacy, policymakers should place more emphasis on responsibility and openness. Additionally, This study is the first to examine CEO characteristics as moderating factors in the context of Indonesia.